Identifikasi Sistem Proteksi Kebakaran Bangunan Gedung Maluku City Mall Ambon - Tuarita, Diva Stelma Risti; Buyang, Christy G; Taihuttu, Felix (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2025)
This research focuses on the identification of fire protection systems in Maluku City Mall Ambon by referring to the Regulation of the Minister of Public Works No. 26/PRT/M/2008 of 2008, located on Jl. Jenderal Sudirman Sirimau, is one of the busiest shopping centers in Ambon city. Considering the high potential risk of fire in this mall, caused by the large number of flammable materials and the use of gas stoves by traders, this study aims to evaluate whether the existing fire protection system meets the standards set in the regulation. To collect data, direct observation was conducted with fire analysis experts using a checklist, as well as interviews with building managers. This study shows that the identification of Protection System components in the Maluku City Mall Ambon Building using the Regulation found that 33 components were available according to the requirements and 11 components were not yet available from 44 protection system components because of the 6 sub-components of Access and Water Supply for extinguishers, only 3 were available according to the regulations, 22 sub-components of Rescue Advice, only 19 were available according to the regulations, 7 sub-components of Passive Protection System, only 4 were available according to the regulations, 9 sub-components of Active Protection System, only 7 were available according to the regulations.